(untitled) (Bangladesh Journal of Medical Science, 2026)
Background Prodromal signs are a valuable factor, but they can be challenging to serve as predictive indicators in schizophrenia; meanwhile, other significant risk factors, like family history and cannabis use, are well-documented high-risk factors. Aim This present study aimed to examine the association between the age at onset of psychosis and prodromal signs, family history of psychosis, and cannabis use independently, as well as the impact of their interaction. Methods Our study employed a retrospective approach and recruited 200 Moroccan patients clinically diagnosed with schizophrenia with a mean age of 31.47 years (± 8.39) from the Ar-razi Psychiatric Center of ibn Sina Hospital. Clinical data were collected in the presence of a qualified psychiatrist via a structured questionnaire. Results we found that the more prodromal signs a patient had, the age at onset of psychosis was slightly lowered with a non-significant small effect [E= -0.04; CI(-0.69) – (0.61); p= 0.89], similarly effect was observed to the presence of family psychosis [E= -0.12; CI(-1.79) – (1.53); p= 0.87], however the cannabis users patients showed a statistically significant association with an earlier age at onset of psychosis by lowering it 2 years compared to non-cannabis users [E= -2.23; CI(-4.28) – (-0.18); p= 0.03], their interaction had also a small effect at the age at onset of psychosis by the presence of prodromal signs. Conclusion cannabis use was associated with an early age at onset of psychosis, and this trend was consistent among patients who exhibited more prodromal signs. Even though other risk factors were non-significant, they also had a small effect influenced by the presence of prodromal signs. BJMS, Vol. 25 No. 01 January’26 Page : 206-213